2009
DOI: 10.1051/0004-6361:200810403
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the optical interferometry observations of HR 4049

Abstract: Aims. We present high spatial resolution observations in the mid-infrared of the dusty core of the binary system HR 4049. Methods. We used the mid-infrared interferometer MIDI/VLTI with 40 m projected baselines. These observations provided two spectrally dispersed visibility curves at a spatial resolution of ∼10 mas. Acquisition images and spectra are in addition obtained with a single telescope spatial resolution of ∼250 mas.Results. The MIDI spectra show features due to emission lines (7.9, 8.6 and 11.3 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This indicates that the PAH emission region is fully resolved by the interferometer, even on the short baseline of 15 m. We estimated a lower limit to the extent of the PAH emission region of 100 mas (64 AU at 640 pc). In line with Menut et al (2009), we conclude that the PAH emission region is not only situated in the disk, although a contribution from the disk is still possible.…”
Section: Pah Emissionsupporting
confidence: 86%
See 1 more Smart Citation
“…This indicates that the PAH emission region is fully resolved by the interferometer, even on the short baseline of 15 m. We estimated a lower limit to the extent of the PAH emission region of 100 mas (64 AU at 640 pc). In line with Menut et al (2009), we conclude that the PAH emission region is not only situated in the disk, although a contribution from the disk is still possible.…”
Section: Pah Emissionsupporting
confidence: 86%
“…Menut et al (2009) analyzed early MIDI observations of HR 4049. They find that the emission region of the PAH 7.7, 8.6, and 11.3 μm features is more extended than that of the underlying continuum.…”
Section: Pah Emissionmentioning
confidence: 99%
“…Dominik et al 2003;Menut et al 2009;Malek & Cami 2014). Apart from a compact disk with a very small temperature range (Dominik et al 2003), a large-scale outflow has been resolved in this source by spatially extended emission of the mid-IR Polycyclic Aromatic Hydrocarbon (PAH) features (e.g.…”
Section: Hr4049 (Nr 7)mentioning
confidence: 99%
“…Sofar, it is not clear whether the PAH carriers reside in the circumbinary disc, or in bipolar lobes created by a more recent mass-loss event, as observed in HR 4049 (Johnson et al 1999;Dominik et al 2003;Antoniucci et al 2005;Hinkle et al 2007;Menut et al 2009) and in the Red Rectangle (Men'shchikov et al 2002;Cohen et al 2004). For HR 4049, Johnson et al (1999) found that the optical polarisation seems to vary with orbital phase, suggesting that the polarisation in the optical is due to scattering in the circumbinary disc.…”
Section: Pah Featuresmentioning
confidence: 99%